Video data collection method for pedestrian movement variables & development of a pedestrian spatial parameters simulation model for railway station environments - Hermant, Laurent Fernand Leon (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.